Government Policy in Managing Covid 19 in Perspective of Human Rights and Social Justice - Alfiah Sabrina; Alijzadilanur Rahma; Alfin Ersa Ardiansyah (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
The state guarantees all residents in Indonesia health. The state also has full responsibility for the fulfilment and provision of health facilities to all its people. It has been almost two years since the COVID-19 pandemic has hit all parts of the world, including Indonesia. The Indonesian government has made various efforts to deal with COVID-19, starting from the implementation of PSBB to emergency PKKM. The government should not need to do the two methods above because the Health Quarantine Law has regulated regional quarantine if an outbreak attacks Indonesia. Healthy living is a right for all Indonesian people who must guarantee the rights of the Indonesian people. It is the state because the state is the holder of full responsibility for its people. Justice is needed in a pandemic situation like today. The government takes the policies so far are still not in line with the interests of the people and always conflict with the people's interests.